2012
DOI: 10.1159/000341887
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Structure and Karyotypic Diversity of the Brazilian Shrew Mouse (<b><i>Blarinomys breviceps</i></b>, Sigmodontinae) in the Atlantic Forest

Abstract: Blarinomys breviceps possesses cryptic and burrowing habits with poorly documented genetics and life history traits. Due to its rarity, only a few specimens and DNA sequences have been deposited in collections worldwide. Here, we present the most comprehensive cytogenetic and molecular characterization of this rare genus. Phylogenetic analyses based on partial cytochrome b sequences were performed, attempting to establish the relationships among individuals with distinct karyotypes along the geographic distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 80 publications
3
21
0
4
Order By: Relevance
“…Such a study would clarify into which of the already known phylogeographic patterns of Atlantic forest mammals (e.g., Colombi et al 2010;Ventura et al 2012;Valdez and D'Elía 2013; see reviews in Martins 2011; Costa and Leite 2012) would A. ruschii fit, or if this species presents a so far undescribed pattern. Similarly, such a study would help assess the alpha diversity of Abrawayaomys (Pardiñas et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Such a study would clarify into which of the already known phylogeographic patterns of Atlantic forest mammals (e.g., Colombi et al 2010;Ventura et al 2012;Valdez and D'Elía 2013; see reviews in Martins 2011; Costa and Leite 2012) would A. ruschii fit, or if this species presents a so far undescribed pattern. Similarly, such a study would help assess the alpha diversity of Abrawayaomys (Pardiñas et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…This scenario is made evident by comparing the degree of conservation in the position and location of this sequence compared with 45S rRNA. Ventura et al (2012) described a similar situation in Akodontini, which shows conservation of 5S rDNA chromosomal sites, despite large chromosomal variability within the group.…”
Section: Discussionmentioning
confidence: 69%
“…Blarinomys breviceps presents a peculiar karyotype and it could not be considered species-specific due to the great variability in 2n and FNa (Geise et al 2008, Ventura et al 2012). Moreover, Ventura et al (2012) suggested the existence of more species for the monotypic genus Blarinomys in Atlantic Forest since molecular phylogenetic analyses showed two geographically distinct lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ventura et al (2012) suggested the existence of more species for the monotypic genus Blarinomys in Atlantic Forest since molecular phylogenetic analyses showed two geographically distinct lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation